AB0814 INDIVIDUAL AND SOCIAL FACTOR CAN INFLUENCE THE QUALITY OF LIFE OF KNEE OA PATIENTS: A SYSTEMATIC REVIEW. (June 2019) - Verges, Josep; Vitaloni, Marianna; Bibas, Marco; Sciortino, Rosa; Quintero, Maritza; Monfort, Jordi; Abajo, Francisco de; Souich, Patrick du; Möller, Ingrid; Oswald, Elizabeth; Matucci-Cerinic, Marco; Eakin, Guy; et al.
Abstract : Background: Knee OA (KOA) is the most common form of chronic joint disease and bears more responsibility than any other disease for disability 1 . It associates with remarkable functional restrictions due to pain. The limitations in activity caused by KOA seriously affect social relationships, emotional well-being, reducing the quality of life (QoL) of patients. The identification of therapies and factors that affects and improve QoL in KOA patients may mitigate the clinical, economic, and social burden of this disease 2 . Thus, the assessment of QoL in KOA is becoming increasingly common in both research and clinical practice 3 . Still a general recompilation of the factors of interest as demographic features, lifestyle characteristics and comorbidity are missing. Objectives: Our aim was to recapitulate the existing information on QoL in KOA patients as an international tool to raise awareness on their condition and guide future actions for patient's management Methods: We conducted a systematic review examining the breadth of the literature regarding the QoL in patients with KOA (up to 2017). We identify articles using MEDLINE, EMBASE, Cochrane, and PsycINFO using relevant keywords as KOA, QoL and well-being and their short forms. All articles were reviewed for inclusion by 3 independent reviewers. QoL domains and items relevant to patients with KOA were extracted. Only original articles were included when containing information on QoL of patients with KOA. Inclusion criteria were QoL compared to one or more demographic factors (e.g., age, gender), lifestyle factor (e.g., functional independence), or comorbidity factor (e.g., diabetes, obesity) or a control group. The quality of included studies was assessed using a quality appraisal tool. Results: We retrieved 610 articles, of which 62 articles fulfilled inclusion criteria for review. Most of the studies were carried out in Europe, American Continent and Asia. The mean of participants in these 62 studies was 561 patients and the majority of them were female, the mean age was 63 years. All the studies described a worse QoL in KOA patients when compared to a control group having women a worst QoL perception than men. A higher BMI, a lower level of physical activity and higher energy expenditure were one of the main factors that correlated with worse QoL. Educational level and higher total mindfulness were shown to improve QoL while poverty, physiological distress, depression and having severely dysfunctional families reduce it. The delivery of a knee self-management program by health care professionals was proven to improve QoL. Finally, surgical KOA interventions generally resulted in good outcomes these results were influenced by individual factors as age, weight, and depression Conclusion: This is the first review pertaining to QoL in KOA patients. KOA has a strong impact on QoL. Individual factors (sex, weight, exercise, mental health, education) can influence QoL. These factors affect treatment outcomes and should be considered for a better patient's management. These data are a valuable tool for health professionals, to better understand the disease and to implement more adequate standard of care. Disclosure of Interests: Josep Verges: None declared, Marianna Vitaloni: None declared, Marco Bibas: None declared, Rosa Sciortino: None declared, Maritza Quintero: None declared, Jordi Monfort Speakers bureau: Bioibérica Procare Health, Francisco de Abajo: None declared, Patrick du Souich: None declared, Ingrid Möller: None declared, Elizabeth Oswald: None declared, Marco Matucci-Cerinic Grant/research support from: Actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: Actelion, BMS; MSD, Janssen, Guy Eakin: None declared, Angie Botto-van Bemden: None declared